Characterization of magnetic field waveforms from triggered lightning attached on transmission line at 18 m, 130 m and 1.55 km. Issue 2 (27th October 2020) - Cai, Li; Li, Jin; Wang, Jianguo; Zhou, Mi; Li, Quanxin; Fan, Yadong
Abstract: The authors present a statistical analysis of characteristics of magnetic fields at different distances from triggered lightning experiments on Transmission Line at Guangdong Comprehensive Observation Experiment on Lightning Discharge during the summer of 2019. The histograms and parameters of statistical distributions for the following 22 waveform characteristics are presented, including current peak, 10%–90% risetime, half‐peak width and steepness, leader magnetic field peak, return‐stroke magnetic field peak, magnetic field peak, 10%–90% risetime, half‐peak width and steepness at 15 m, 130 m and 1.55 km. The arithmetic mean of 48 return stroke current peaks is 18.3 kA and the geometric mean is 17.0 kA. The arithmetic and geometric means of the current 10%–90% risetime are 0.6 and 0.6 μs, respectively. The leader magnetic field, return‐stroke magnetic field and magnetic field peak at 18 m, 130 m and 1.55 km are shown linear relationship with current peak values. With increasing the distance(r), the magnetic field peak value decrease, combining the magnetic field characteristics reported by previous studies, the analysis of all magnetic field peaks in different distances suggest linear relationship with r −0.90 . The magnetic field 10%–90% risetime shows linear relationship with ln(r) and half‐peak width did not show significant correlation with distance.